COMPARATIVE ANALYSIS OF CONSUMER SATISDACTION IN IDELA FAMILY KARAOKE WITH BARATA KARAOKE IN BIMA CITY - Agus Sanjaya; Sri Ernawati (STIESA Press, 2020)
The purpose of this study was to determine and analyze whether there are differences in the level of customer satisfaction at Ideal Family Karaoke with Barata Karaoke Bima city.The type of research used is comparative, the population in this study are consumers of karaoke service users in Ideal Family karaoke and Barata karaoke whose numbers are not yet known with certainty. The sample used is 30 visitors or consumers, with a sampling technique that is accidental sampling. The instrument used was a Likert scale questionnaire. Data analysis method with Paired Samples Test. Based on the results of the analysis of the data that has been done it can be concluded that there is no no difference between the ideal satisfaction of consumers Family Karaoke with customer satisfaction Barata Karaoke Bima city.